2018
DOI: 10.1021/acs.cgd.8b00893
|View full text |Cite
|
Sign up to set email alerts
|

Highest Reported Denticity of a Synthetic Nucleoside in the Unprecedented Tetradentate Mode of Acyclovir

Abstract: The unprecedented tetradentate, chelating, and μ3-bridging mode of acyclovir (acv) drives to a 1D-polymeric ribbon in [{Cu2(acv)­(μ3-acv)­(SO4)­(μ2-SO4)­(H2O)4}·H2O·MeOH] n , stabilized by μ2-SO4 ligands, interligand H-bonds, and anion/π-(SO4/acv) interactions. Stacking π,π-(acv/μ3-acv) interactions play a key role in the crystal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Along the past decades, mainly three research groups have contributed to enlighten the metal binding abilities of acyclovir [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. According to this information, acv preferentially acts as monodentate ligand, involving the purine moiety, with the M-N7(acv) coordination bond acting in cooperation with an intramolecular interligand D-H···O6(acv) interaction (D = oxygen or nitrogen H-donor atoms) [ 8 , 10 , 11 , 13 , 16 , 18 , 19 , 20 , 21 , 22 ]. Besides this preferred molecular recognition pattern, further studies have reported more unconventional modes for acv such as the N7,O6-chelating mode or even the tetradentate μ 3 -N7,O6,O(e),O(ol) mode [ 12 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along the past decades, mainly three research groups have contributed to enlighten the metal binding abilities of acyclovir [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. According to this information, acv preferentially acts as monodentate ligand, involving the purine moiety, with the M-N7(acv) coordination bond acting in cooperation with an intramolecular interligand D-H···O6(acv) interaction (D = oxygen or nitrogen H-donor atoms) [ 8 , 10 , 11 , 13 , 16 , 18 , 19 , 20 , 21 , 22 ]. Besides this preferred molecular recognition pattern, further studies have reported more unconventional modes for acv such as the N7,O6-chelating mode or even the tetradentate μ 3 -N7,O6,O(e),O(ol) mode [ 12 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review emphasizes the relevance of the N(heterocyclic)-H tautomeric possibilities in neutral and protonated forms of such kinds of natural or synthetic closely related N-heterocyclic ligands. Recent reports from our groups extend these points of view to the guanine-synthetic acyclovir as a ligand [52][53][54]. Now we have the opportunity to deep into the relevance of these factors on the basis of the available crystallographic results related to cationic forms of Hdap, its salts and inner-or out-sphere metal complexes.…”
Section: Structural Insides On N(heterocyclic)-proton Affinities H-tmentioning
confidence: 97%
“…This role will cooperate with other N or O donors of both nucleosides. The maximum expression of this is provided by the acv-H anion (which coexists with molecular acv) in the polymer DIDJUY [9]. It should also be noted that, while O6-acv is involved as H-acceptor in intramolecular interligand H-bonds, the H-atoms of the exocyclic -N(6)H 2 group of 9heade make it a hydrogen donor in such interactions.…”
Section: Introductionmentioning
confidence: 99%